Activation of Tripartite Motif Containing 63 Expression by Transcription Factor EB and Transcription Factor Binding to Immunoglobulin Heavy Chain Enhancer 3 Is Regulated by Protein Kinase D and Class IIa Histone Deacetylases - Pablo Tortola, Cristina; Fielitz, Britta; Li, Yi; Rüdebusch, Julia; Luft, Friedrich C.; Fielitz, Jens (Frontiers in Physiology, 2021)
Rationale: The ubiquitin proteasome system (UPS) is responsible for skeletal muscle atrophy. We showed earlier that the transcription factor EB (TFEB) plays a role by increasing E3 ubiquitin ligase MuRF1/TRIM63 expression. MuRF1 ubiquitinates structural proteins and mediates their UPS-dependent degradation. We now investigated how TFEB-mediated TRIM63 expression is regulated. Objective: Because PKD1, HDAC5, and TFEB belong to respective families with close structural, regulatory, and functional properties, we hypothesized that these families comprise a network regulating TRIM63 expression. Methods and Results: We found that TFEB and TFE3 activate TRIM63 expression. The class IIa HDACs HDAC4, HDAC5, and HDAC7 inhibited this activity. Furthermore, we could map the HDAC5 and TFE3 physical interaction. Protein kinase D (PKD)1, PKD2, and PKD3 reversed the inhibitory effect of all tested class IIa HDACs towards TFEB and TFE3. PKD1 mediated nuclear export of all HDACs and lifted TFEB and TFE3 repression. We also mapped the PKD2 and HDAC5 interaction. We found that the inhibitory effect of PKD1 and PKD2 towards HDAC4, HDAC5 and HDAC7 was mediated by their phosphorylation and 14-3-3 mediated nuclear export. Conclusions: TFEB and TFE3 activate TRIM63 expression. Both transcription factors are controlled by HDAC4, HDAC5, HDAC7, and all PKD-family members. We propose that TRIM63 expression is tightly controlled by the multilevel PKD//HDAC//TFEB/TFE3 network.